2018
DOI: 10.1002/smll.201802570
|View full text |Cite
|
Sign up to set email alerts
|

Li‐Rich Li[Li1/6Fe1/6Ni1/6Mn1/2]O2 (LFNMO) Cathodes: Atomic Scale Insight on the Mechanisms of Cycling Decay and of the Improvement due to Cobalt Phosphate Surface Modification

Abstract: Lithium-rich Li[Li Fe Ni Mn ]O (0.4Li MnO -0.6LiFe Ni Mn O , LFNMO) is a new member of the xLi MnO ·(1 - x)LiMO family of high capacity-high voltage lithium-ion battery (LIB) cathodes. Unfortunately, it suffers from the severe degradation during cycling both in terms of reversible capacity and operating voltage. Here, the corresponding degradation occurring in LFNMO at an atomic scale has been documented for the first time, using high-angle annular dark-field scanning transmission electron microscopy (HAADF-ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 114 publications
2
10
0
Order By: Relevance
“…Our previous works indicated that voltage fade was significantly suppressed by replacing Co with Fe 35,36 . Unfortunately, the low coulombic efficiency during cycling has always existed but is rarely reported in Fe-substituted Li-rich cathode materials 20,[43][44][45] , which inevitably gives rise to poor cyclic performance and reduces battery life. In order to intuitively investigate the mechanism of low CE of LNFMO, the LNFMO electrodes were cycled in different concentrations of electrolyte at 0.1 C (20 mA g −1 ).…”
Section: Characterization Of Lnfmomentioning
confidence: 99%
“…Our previous works indicated that voltage fade was significantly suppressed by replacing Co with Fe 35,36 . Unfortunately, the low coulombic efficiency during cycling has always existed but is rarely reported in Fe-substituted Li-rich cathode materials 20,[43][44][45] , which inevitably gives rise to poor cyclic performance and reduces battery life. In order to intuitively investigate the mechanism of low CE of LNFMO, the LNFMO electrodes were cycled in different concentrations of electrolyte at 0.1 C (20 mA g −1 ).…”
Section: Characterization Of Lnfmomentioning
confidence: 99%
“…To ensure better interphase stability and improve the Li + diffusion, the surface of the MNC sample is firstly modified by a simple reported ionized solution coating method (ST-MNC) [ 40 ]. We chose Co-containing coating layers for the surface treatment considering that they contribute to improve the electrochemical performance of layered cathodes [ 26 , 40 ]. It has been reported that the using the completely ionized solution with lithium and cobalt acetate in ethanol to conduct the surface treatment could result in a stable Li x CoO 2 phase after heating treatment [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, surface modification has been found to be effective as it can not only inhibit the phase transition and side reactions with the electrolytes or hydrogen fluoride, but also provide ion or/and electron highways in some cases [19][20][21][22][23][24][25][26]. Ion conductive coating materials such as Al 2 O 3 [21], AlF 3 [23,27], and phosphates [26] have been proved to facilitate ion diffusion and enhance the rate capability. Also, electron conductive materials such as carbon [22] and polypyrrole [25] have revealed the ability to accelerate charge transfer kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…LFP has a stable olivine structure and has attracted significant interest [12][13][14][15] due to low cost as it does not contain cobalt, has high average voltage and a low susceptibility to thermal runaway compared to NCM and LCO, providing a good balance between performance and safety [16][17][18]. To date, cathode materials with high capacity and voltage such as nickel- [19][20][21][22][23][24], manganese- [25] and lithium-rich [19,[25][26][27][28][29][30][31] materials, carbon-coated LFP nanospheres [32] and vanadium pentoxide [33] have been recognized. Higher contents of nickel and lithium increase the specific capacity of the cathode material but decrease thermal stability.…”
Section: Cathodementioning
confidence: 99%